Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 Infection Among Children in Summer Schools Applying Stringent Control Measures in Barcelona, Spain. (12th March 2021) - Jordan, Iolanda; Fernandez de Sevilla, Mariona; Fumado, Victoria; Bassat, Quique; Bonet-Carne, Elisenda; Fortuny, Claudia; Garcia-Miquel, Aleix; Jou, Cristina; Adroher, Cristina; Melé Casas, María; Girona-Alarcon, Mònica; Hernández Garcia, María; et al.
Abstract: Background: Understanding the role of children in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission is critical to guide decision-making for schools in the pandemic. We aimed to describe the transmission of SARS-CoV-2 among children and adult staff in summer schools. Methods: During July 2020, we prospectively recruited children and adult staff attending summer schools in Barcelona who had SARS-CoV-2 infection. Primary SARS-CoV-2 infections were identified through (1) a surveillance program in 22 summer schools of 1905 participants, involving weekly saliva sampling for SARS-CoV-2 reverse-transcription polymerase chain reaction (RT-PCR) during 2–5 weeks; and (2) cases identified through the Catalonian Health Surveillance System of children diagnosed with SARS-CoV-2 infection by nasopharyngeal RT-PCR. All centers followed prevention protocols: bubble groups, handwashing, face masks, and conducting activities mostly outdoors. Contacts of a primary case within the same bubble were evaluated by nasopharyngeal RT-PCR. Secondary attack rates and the effective reproduction number in summer schools (Re*) were calculated. Results: Among the >2000 repeatedly screened participants, 30 children and 9 adults were identified as primary cases. A total of 253 close contacts of these primary cases were studied (median, 9 [interquartile range, 5–10] for each primary case), among which 12 new cases (4.7%) were positive for SARS-CoV-2. The Re* was 0.3, whereas the contemporary rate in the general population from the same areas in Barcelona was 1.9. Conclusions: The transmission rate of SARS-CoV-2 infection among children attending school-like facilities under strict prevention measures was lower than that reported for the general population. This suggests that under preventive measures schools are unlikely amplifiers of SARS-CoV-2 transmission, supporting current recommendations for school opening. Abstract : Transmission rates among children and adults in summer school settings, implementing strict preventive measures, were low in comparison with community transmission rates. These results support current policies of keeping schools open for children's benefit, under strict preventive measures.